2019
DOI: 10.1080/15384101.2019.1609818
|View full text |Cite
|
Sign up to set email alerts
|

Sirt2 epigenetically down-regulates PDGFRα expression and promotes CG4 cell differentiation

Abstract: We have previously found that Sirt2 enhanced the outgrowth of cellular processes and MBP expression in CG4 cells, where Sirt2 expression is suppressed by transcription factor Nkx2.2. However, the detailed mechanism of Sirt2 facilitating oligodendroglial cell differentiation remained unclear. In the present study, we observed that Sirt2 partially translocated into the nuclei when CG4 cells were induced to differentiate. Sirt2 was detected at the CpG island of PDGFRα promoter via ChIP assay during the cells diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Different from functions of the above genes in myogenesis, PDGFRα + mesenchymal progenitors were the major contributor to ectopic fat formation in skeletal muscle [ 37 ], and embryonic adipose progenitor cells without PDGFRα would undergo fate change from adipogenic to fibrotic lineage [ 64 ]. Although DNA methylation-induced PDGFRα and FGFR2 silencing has been reported in CG4 cells [ 65 ] or primary human pituitary adenomas [ 66 ], the role of DNA methylation in regulating the expression level of these co-different genes and their effects on myogenesis or adipogenesis still remains unclear. Unlike the well-known functions of the above genes in ectopic fat accumulation and skeletal muscle development, the function of CNCNA2D2 in relation to skeletal muscle development and homeostasis has been sparsely described in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Different from functions of the above genes in myogenesis, PDGFRα + mesenchymal progenitors were the major contributor to ectopic fat formation in skeletal muscle [ 37 ], and embryonic adipose progenitor cells without PDGFRα would undergo fate change from adipogenic to fibrotic lineage [ 64 ]. Although DNA methylation-induced PDGFRα and FGFR2 silencing has been reported in CG4 cells [ 65 ] or primary human pituitary adenomas [ 66 ], the role of DNA methylation in regulating the expression level of these co-different genes and their effects on myogenesis or adipogenesis still remains unclear. Unlike the well-known functions of the above genes in ectopic fat accumulation and skeletal muscle development, the function of CNCNA2D2 in relation to skeletal muscle development and homeostasis has been sparsely described in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 78 Nevertheless, these studies are based on the inhibition of Stat1 pathway in all somatic cells, the influence of Stat1 pathway regulation on remyelination specifically in microglia needs further study. Although the factors such as Pdgfa and Pdgfb secreted by microglia and receptor Pdgfra, Gpr37l1 on OPCs can hinder the differentiation of OPCs, 43 , 48 functional changes revealed by GO analysis in aged OPCs showed no hint of their roles. However, our analysis did not exclude their possible influences and more efforts are needed for further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…37,43 Apoe, App, Pdgfa, Pdgfb and Sdc4 were included in the myelin impediment group (Figure 6B) due to their potential hindrance in OPC differentiation. 48,49 Beneficial cytokines Vegfb and Igf1 did not show significantly high expression in activated microglia (Figure 6B). Subsequently, we attempted to identify several regulatory factors that can upregulate those factors in the myelin promotion group and down-regulate those factors in the myelin impediment group.…”
Section: Regulation Of Stat1 Might Reverse Aged Microglia To Promote Remyelinationmentioning
confidence: 92%
“…Cytoplasmic Sirt2 deacetylates multiple proteins, including alpha-tubulin in cultured OPCs 19 and HeLa cells 20 , as well as the polarity protein Par-3 in Schwann cells 21 . Sirt2 also suppressed PDGFRα expression after translocation to the nucleus, promoting differentiation of the CG4 glial cell line 22 . In addition, a recent study found that Sirt2 is delivered to axons from OL to promote mitochondrial ATP production 23 .…”
Section: Introductionmentioning
confidence: 94%